Examining Uganda’s Legal and Institutional Framework in Curbing Book Piracy - Kaddu, Sarah; Chelangat, Jospert; Haumba, Eric Nelson (Ghana Library Journal, 2022)
This paper examines the legal framework for curbing book piracy in Uganda. The paper sought to address the following objectives: to establish the forms of book piracy practiced; to establish the existing legal frameworks and efforts to curb book piracy; investigate the level of awareness of the legal framework among book printers and its implications on book piracy; to examine the scope of counter-piracy enforcement powers and the law; to identify the setbacks in the enforcement of the legal framework on book piracy. A case study research design and qualitative research paradigm were adopted. Focus Group Discussions (FGDs), unstructured interviews and Document reviews were the data collection methods. The study findings reveal that: duplication, circumventing e-Books and plagiarism are the common forms of book piracy practiced; the legal and institutional frameworks are in place putting in efforts such as awareness and sensitization, engagement with universities, and promotion of the use of holograms; book printers were found to be moderately aware of the legal framework, but they were not deeply knowledgeable of many provisions of the laws; the laws as they are, are ineffective. The setbacks in the enforceability included: the high cost of registration, difficulty in differentiating between genuine and pirated books. The study concludes that different forms of book piracy are practiced in Uganda and that efforts are being undertaken to avert the practice. The study recommends the revision of the existing legal framework; adoption and promotion of security features and restructuring of the copyright registration process among others.